Evaluation and Implementation of integrated care program for multimorbid patients within ACT@Scale project - Basque health service (Osakidetza) - Ane Fullaondo; Danika Schepis; Irati Erreguerena; Consortium ACT@Scale; Rosa Gonzales2; Ana Porta; Inmaculada Moro; Igor Zabala; Jon Txarramendieta; Esteban de Manuel (International Journal of Integrated Care, 2019)
Introduction: The aging of the population and the increase in chronic patients represent a huge challenge for the sustainability of all healthcare systems. The Basque governance has dedicates time and resources to tackle this problem. One of the initiatives is represented by the Basque Health Service´s integrated intervention for multimorbid population program within ACT@Scale project. Theory/Methods: The program follows the multi-organizational structured collaborative quality improvement methods based on Plan-Do-Study-Act (PDSA) cycle.  Applying the PDSA methodology, the latest achievements have been: Create a scorecard to evaluate the care pathway effectiveness Generate training sessions on several aspects related to the care pathway Results: Scorecard definition Dimensions 1- Resources 2- Services 3- Care Integration 4- Effectiveness 5- Safety 6- Equality 7- Efficiency ImplementationDesign of on-line staff training programs in: 1- Patients Empowerment program, Kronik-On 2- Risk Stratification approach and tools Discussions: The program is already up and running in Osakidetza. These new achievements will facilitate the coverage of almost 15000 patients by the end of 2019. We believe these new results will promote the scaling-up of the program and, at the same time, it will help measure and evaluate the process effectiveness. A central engine will help in data storage and extraction. Conclusions: The team has defined and described the indicators necessary to periodically evaluate the care pathway effectiveness. This scorecard is a result of a broad consensus among Osakidetza’s healthcare professionals. The training program has been realized taking into account the healthcare professionals needs and structured according to Osakidetza Department of education’s guidelines. Lessons learned: In order to obtain sustainable results it is important to take into account: Specific organizational peculiarity The stakeholder’s needs The implementation has to be simple Limitations: Indicators need to be tested and eventually reshaped in six months/one year. The Integrated program management system is not fully operative yet. Suggestions for future research: The multimorbid program has been deployed in all local organizations. With these new tools we will be able to evaluate the effectiveness of it and we will provide health professionals will the suitable information/training to perform their daily activity within the program. We will need to study the results of this program in six months/one year, and possibly tune the indicators accordingly.